Partial long-term clinical improvement after a BCG challenge in systemic lupus erythematosus-prone mice - Mora, Valentina P. (2024)
Systemic Lupus Erythematosus (SLE) is an autoimmune disorder that causes a breakdown of immune tolerance. Current treatments mainly involve general immunosuppression, increasing the risk of infections. On the other hand, Bacillus Calmette-Guérin (BCG) has been investigated as a potential therapy for autoimmune diseases in recent years, prompting an ongoing investigation. This study aimed to evaluate the effect of BCG vaccination on early and late clinical presentation of SLE in a murine disease model. MRL/MPJ-Faslpr mice were immunized with BCG or treated with PBS as a control. The progress of the disease was evaluated at 27 days post-immunization (dpi) (early) and 56 dpi (late). Clinical parameters and proteinuria were monitored. Blood samples were collected for measurement of antinuclear antibodies (ANAs), anti-double-stranded DNA (anti-dsDNA), and cytokine determination was performed using ELISA. Samples collected from mice were analyzed by flow cytometry and histopathology. We observed a clinical improvement in BCG-treated mice, reduced proteinuria in the latter stages of the disease, and decreased TNF-α. However, BCG did not elicit significant changes in ANAs, anti-dsDNA, histopathological scores, or immune cell infiltration. BCG was only partially beneficial in an SLE mouse model, and further research is needed to determine whether the immunity induced by this vaccine can counteract lupus´s autoimmune response.